Labor Productivity, Firm-size and Gender : The Case of Informal Firms in Argentina and Peru - Amin, Mohammad (World Bank, Washington, DC, 2021)
A commonly held view is that female-owned businesses suffer from many disadvantages compared to male-owned businesses. These disadvantages lead, in turn, to relatively lower levels of efficiency and smaller firm-size among female-owned businesses—the female owned firms under-performance hypothesis. Using data on unregistered firms in Argentina and Peru, the female-owned firms under-performance hypothesis is confirmed. The gender based difference in efficiency and firm-size holds within the full sample and no more than 25 percent to 30 percent of the difference can be explained by variations in firm characteristics. The gender based gap in performance also holds within various sub-samples of firms, although the magnitude of the difference does vary across the sub-samples.